Envolvimento da neurotransmissão ocitocinérgica do núcleo paraventricular do hipotálamo na modulação da ansiedade e nocicepção induzidas pelo convívio com o coespecífico com dor crônica em camundongos machos e fêmeas - Ribeiro, Heloísa Máximo (Universidade Federal de São Carlos, 2025)
Pain is considered a “sensory and emotional experience” that may or may not be related to tissue damage. Empathy is defined as “the sharing of emotions between individuals and the adoption of the other individual's point of view”, which is fundamental to their coexistence. Studies show that mice living with a partner in chronic pain exhibit increased anxiety-like behaviors and hypernociception. Oxytocin, a neurohormone agonist of oxytocinergic receptors, produced and released by the hypothalamus-neurohypophysis system, is involved in affective processes, stress, cognition and social behavior, and its reduction is related to psychiatric disorders such as depression and anxiety. The paraventricular nucleus of the hypothalamus (PVN) is one of the sites of oxytocin production. Considering that nociceptive processes promote an increase in oxytocin synthesis in the PVN, and that living with a partner with chronic pain promotes an increase in FosB in the same region, this study aimed to evaluate the involvement of oxytocinergic neurotransmission in the PVN in the modulation of anxiety and nociception induced by living with a partner with chronic pain in male and female mice. To this end, male and female Swiss-Albino mice were housed in quartets after weaning. In each quartet, one animal underwent sciatic nerve constriction surgery, becoming a pain demonstrator, or similar surgery, becoming a Sham control, after 14 days of cohabitation. The observer animals (Ob-Sham and Ob-CNC) had a cannula implanted in the skull, directed to the PVN, and on the 28th day of the experiment received intra-PVN injections of saline 0.9%, oxytocin (1.0 µg/0.1µL) and/ or atosiban (0.4 µg/0.1µL, oxytocin receptor biased antagonist). Subsequently, they were evaluated in the EPM and by the writhing test for anxiety-like behaviors and nociception, respectively. As a result, living with a conspecific with pain promoted hypernociception in males and females, and increased anxiety-like behaviors in males. In addition, intra-PVN injections of oxytocin were able to reverse hypernociception in both sexes. Regarding anxiety-like behaviors, oxytocin failed to reduce them in males but did reduce them in Ob-CNC females compared to the Ob-CNC saline control. Atosiban reduced hypernociception in males and changed some behaviors assessed in the EPM of males and females. Combined injections of atosiban and oxytocin in males tended to increase anxiety-like behaviors in Ob-Sham and reduce it in Ob-CNC, with no effect on nociception. Therefore, the present study found evidence of the participation of the PVN oxytocinergic system in the control of hypernociception and anxiety-like behaviors in male and female mice that lived with a conspecific in chronic pain.
The role of oxytocinergic neurotransmission of the paraventricular nucleus of the hypothalamus (PVN) in modulating anxiety and nociception induced by interaction with conspecific undergoing chronic pain in male and female mice
Keywords: Empatia; Dor; Ansiedade; Fêmeas; Camundongos; Ocitocina; PVN; Atosibana; Empathy; Pain; Anxiety-like behaviors; Females; Mice; Oxytocin; Atosiban; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::NEUROFISIOLOGIA; CIENCIAS BIOLOGICAS::FARMACOLOGIA::NEUROPSICOFARMACOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COMPARATIVA::MECANISMOS INSTINTIVOS E PROCESSOS SOCIAIS EM ANIMAIS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::ESTIMULACAO ELETRICA E COM DROGAS; COMPORTAMENTO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::PSICOBIOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::NEUROLOGIA, ELETROFISIOLOGIA E COMPORTAMENTO